Formation of Fuel Plantations with Kumri in Dry Areas - Sweet, J. M. (Indian Forester, 1946)
We cannot afford to carry out intensive regeneration work in dry areas (except those that are very close to centres of demand) unless most of the work is done for us free of cost by "kumridars." "Kumridars" will not be forthcoming unless they can be sure of at least two years unrestricted cultivation before we put in our forest crop. In very dry localities they should be given three years. If this policy is adopted, not only will the cultivator be benefitted, and through him the country as a whole, but we shall stand a much better chance of raising successful fuel forests than we do at present.